The Influence of Virtual Lab, Gamification, and Augmented Reality on Students' Understanding of Microbiology Concepts - Ananta, Yorasakhi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This article is a literature study that aims to examine the effect of the use of Virtual Lab, Gamification, and Augmented Reality (AR) on students' understanding of microbiology concepts. Along with the development of technology in the world of education, conventional learning methods have undergone significant transformations. Virtual Lab allows microbiology practicums to be carried out simulatively, Gamification encourages learning motivation through game elements, and AR visualizes complex microbiology objects interactively. This study collects and analyzes the results of previous studies that are relevant in the context of higher education. The results of the study show that the three technological approaches are generally able to improve students' understanding of microbiology concepts, increase interest in learning, and strengthen critical thinking skills. However, the success of its implementation is highly dependent on the readiness of the institution, the competence of lecturers, and the characteristics of students.